Validação de método qualitativo para detecção de soja Roundup Ready® em grãos de soja por Nested PCR (reação em cadeia da polimerase) - Carolina Sheng Whei Miaw (2013)
Considering the expansion of genetically modified soybean and the basic principle of consumers right to access information about the products, the Brazilian and other countries legislation establishes a limit of genetically modified organisms to label transgenic food. Qualitative tests based on polymerase chain reaction (PCR) have been recommended such as Nested PCR. However, validation of qualitativemethods, important to confirm the reliability of analytical results, is still a critical point in the quality management of food analysis laboratories. The objective of this project was to validate an in-house method for qualitative detection of Roundup Ready (RR®) soy in soybeans by Nested PCR. Samples of soy containing from 0.001 to 1 % of RR® and blank samples were analyzed. Techniques for quantification of the deoxyribonucleic acid (DNA), agarose gel electrophoresis and fluorimetry, were compared. The false-positive rate was zero, with selectivity and reliability rates of 100.0% for both techniques, demonstrating selectivity of the method. Sensitivity and reliability rates ranged between 23.3 and 100.0% (agarose gel) and between 30.0 and 100.0% (fluorimetry). 100.0% positive results were obtained for all levels above 0.030%, indicating sensitivity. Estimated detection limits for the techniques of agarose gel electrophoresis and fluorimetry were 0.007 and 0.005 %, respectively. The method was considered selective for maize events Bt11 and GA21 and robustfor different concentrations of target DNA and brands of Taq DNA polymerase. Analysis of commercial samples collected by the Health Surveillance of Minas Gerais State demonstrated the applicability of the method. The method was fitness for purpose, considering the maximum limit recommended for genetically modified organisms in national and international legislation.